MANAJEMEN KREDIT USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Hesti Respatiningsih (SEGMEN Jurnal Manajemen dan Bisnis, 2011)
The core of the problem which is faced by small and medium enterprise is the available capital to run its business. The lock of capital can be obtained from the loan from others financial providers. This credit can be expected to be one of the important instrument in developing in small and medium enterprise business. Therefore, it is needed the professional credit management in credit management. Credit management is the providing credit management from the beginning credits until the repayment. Keywords: capital, credit, small and medium enterprise, credit management.